Effect of hydrogen and oxygen addition as a mixture on emissions and performance characteristics of a gasoline engine - Karagoz, Y.; Yuca, N.; Sandalci, T.; Dalkilic, A. S. (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Use of hydrogen in spark ignition engines as supplementary fuel can be preferred due to improved combustion characteristics and emission advantages. However, hydrogen storage and production difficulties under the hood limit the use of it in internal combustion engines (ICES). In this study, a different approach was used to overcome these difficulties. Hydrogen and oxygen gas mixture was produced by electrolyser and consumed simultaneously to eliminate the necessity of a storage device. Firstly, a practical alkaline water electrolyser was designed and manufactured to produce hydrogen from water to be subsequently used in ICE as a supplementary fuel. In order to optimize electrolyser, the parameters of gap between plates, concentration of solution and voltage were kept under control. Then, H-2/O-2 gas mixture used as secondary fuel in SI engine was generated by electrolyser on optimized operating conditions. 0 and 20 l/min H-2/O-2 mixture as supplementary fuel was introduced into intake manifold of engine using gas injectors where 0 l/min refers to without hydrogen case and 20 l/min with hydrogen case. According to the results, the brake power and brake thermal efficiency were increased by means of hydrogen addition. Besides, total hydrocarbon and carbon monoxide emissions decreased, whereas the dramatic increase of nitrogen oxides emissions couldn't be prevented during the experimental work. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: SI engine; Additional fuel; Electrolysis; Emission; Combustion; LEAN-BURN; EXHAUST EMISSIONS; DUAL FUEL; Chemistry; Electrochemistry; Energy & Fuels